Ancient West Mexicos : time, space, and diversity - Englehardt, Joshua; Heredia Espinoza, Verenice Y.; Beekman, Christopher (University Press of Florida, 2020)
"This volume highlights the diversity and complexity of western Mexico's pre-Hispanic cultures and argues that the region was more similar than many researchers have believed to the rest of the Mesoamerican world"--